Efektivitas Pemberian Telur dan Vitamin C terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III - Ulpah Ulpah; Acmad Fauzi (Universitas Malahayati Lampung, 2023)
ABSTRACT One of the nutritional disorders that often occur in pregnant women is anemia. Cases of anemia of pregnant women in the Ciomas Health Center Work Area in the last three years (2018-2020) have increased with an average percentage of cases of 60.9%. Efforts to prevent anemia is to consume Fe tablets that can be combined with herbal complementary therapies, one of which is consuming eggs and vitamin C with the aim of increasing hemoglobin levels. It is known that the effectiveness of giving eggs and vitamin C to increase hemoglobin levels in pregnant women in the third trimester of pregnancy in the Ciomas Health Center Work Area of Serang Regency in 2022. The research method uses quasi eksperiments with pretest and posttest with control group designs. The sample in the study was 46 third trimester pregnant women, 23 pregnant women with mild anemia were given boiled eggs and 22 pregnant women with mild anemia were given vitamin C. Sampling techniques using purposive sampling. Bivariate analysis uses dependent t-test and independent t-test. The average hemoglobin level of the intervention group before egg administration was 10.46 gr/dl and after the consumption of boiled eggs 12.34 gr/dl. The average hemoglobin levels of the control group before vitamin C administration were 10.45 grams/dl and after taking vitamin C 11.45 gr/dl. Consumption of eggs and vitamin C effectively increases hemoglobin levels of pregnant women with anemia (p = 0.000). The provision of eggs and vitamin C is effective in increasing hemoglobin levels in pregnant women in the third trimester of pregnancy in the Ciomas Health Center Work Area. Pregnant women with mild anemia are recommended to consume Fe tablets regularly accompanied by consuming eggs and vitamin C every day to increase hemoglobin levels more quickly. Keywords: Anemia, Hemoglobin, Egg Feeding and Vitamin C ABSTRAK Salah satu gangguan gizi yang sering terjadi pada ibu hamil adalah anemia. Kasus anemia ibu hamil di Wilayah Kerja Puskesmas Ciomas dalam tiga tahun terakhir (2018-2020) mengalami peningkatan dengan rata-rata persentase kasus sebesar 60,9%. Upaya pencegahan anemia adalah dengan mengkonsumsi tablet Fe yang dapat dikombinasikan dengan terapi komplementer herbal salah satunya dengan mengkonsumsi telur dan vitamin C dengan tujuan untuk meningkatkan kadar hemoglobin. Diketahui efektivitas pemberian telur dan vitamin C untuk meningkatkan kadar hemoglobin pada ibu hamil trimester III kehamilan di Wilayah Kerja Puskesmas Ciomas Kabupaten Serang tahun 2022. Metode penelitian menggunakan quasi eksperiments dengan pretest and posttest with control group design. Sampel dalam penelitian adalah 46 ibu hamil trimester III, 23 ibu hamil anemia ringan diberikan telur rebus dan 22 ibu hamil anemia ringan diberikan vitamin C. Teknik pengambilan sampel menggunakan purposive sampling. Analisis bivariat menggunakan uji-t dependen dan uji-t independen. Rerata kadar hemoglobin kelompok intervensi sebelum pemberian telur 10,46 gr/dl dan setelah konsumsi telur rebus 12,34 gr/dl. Rerata kadar hemoglobin kelompok kontrol sebelum pemberian vitamin C adalah 10,45 gram/dl dan setelah pemberian vitamin C 11,45 gr/dl. Konsumsi telur dan vitamin C efektif meningkatkan kadar hemoglobin ibu hamil dengan anemia (p = 0,000). Pemberian telur dan vitamin C efektif dalam meningkatkan kadar hemoglobin pada ibu hamil trimester III kehamilan di Wilayah Kerja Puskesmas Ciomas. Ibu hamil dengan anemia ringan dianjurkan untuk mengkonsumsi tablet Fe secara teratur disertai dengan mengkonsumsi telur dan vitamin C setiap hari untuk meningkatkan kadar hemoglobin lebih cepat. Kata Kunci: Anemia, Hemoglobin, Pemberian Telur dan Vitamin C